Non-invasive assessment of ventriculo-arterial coupling using aortic wave intensity analysis combining central blood pressure and phase-contrast cardiovascular magnetic resonance. (9th September 2019) - Bhuva, Anish N; D'Silva, A; Torlasco, C; Nadarajan, N; Jones, S; Boubertakh, R; Van Zalen, J; Scully, P; Knott, K; Benedetti, G; Augusto, J B; Bastiaenen, Rachel; et al.
Abstract: Background: Wave intensity analysis (WIA) in the aorta offers important clinical and mechanistic insight into ventriculo-arterial coupling, but is difficult to measure non-invasively. We performed WIA by combining standard cardiovascular magnetic resonance (CMR) flow-velocity and non-invasive central blood pressure (cBP) waveforms. Methods and results: Two hundred and six healthy volunteers (age range 21–73 years, 47% male) underwent sequential phase contrast CMR (Siemens Aera 1.5 T, 1.97 × 1.77 mm 2, 9.2 ms temporal resolution) and supra-systolic oscillometric cBP measurement (200 Hz). Velocity ( U ) and central pressure ( P ) waveforms were aligned using the waveform foot, and local wave speed was calculated both from the PU-loop ( c ) and the sum of squares method ( c SS). These were compared with CMR transit time derived aortic arch pulse wave velocity (PWVtt ). Associations were examined using multivariable regression. The peak intensity of the initial compression wave, backward compression wave, and forward decompression wave were 69.5 ± 28, −6.6 ± 4.2, and 6.2 ± 2.5 × 10 4  W/m 2 /cycle 2, respectively; reflection index was 0.10 ± 0.06. PWVtt correlated with c or c SS ( r  =   0.60 and 0.68, respectively, P  < 0.01 for both). Increasing age decade and female sex were independently associated with decreased forward compression wave (−8.6 and −20.7 W/m 2 /cycle 2, respectively, P  < 0.01) and greater wave reflection index (0.02 and 0.03, respectively, P  < 0.001). Conclusion: This novel non-invasive technique permits straightforward measurement of wave intensity at scale. Local wave speed showed good agreement with PWVtt, and correlation was stronger using the c SS than the PU-loop. Ageing and female sex were associated with poorer ventriculo-arterial coupling in healthy individuals.